Enhancement of PAPR Abatement for FBMC System - Venusamy, Kanagaraj; Muthuramalingam, Malarvizhi; S. Kannadhasan; R. Vanithamani (International Journal of Intelligent Systems and Applications in Engineering, 2023)
Even though FBMC is a candidate waveform for fifth generation technology, it has major drawbacks that high PAPR (Peak to Power Average Ratio) which causes nonlinearity in power amplifiers and cost inefficiency. It also leads to signal degradation and results in harmonics. Therefore, much method has been used to reduce Peak power of filter bank multicarrier system. In this paper detailed analysis of effect of PAPR in multicarrier system and gradual improvement of PAPR reduction is discussed. Particularly effects of DFT (discrete Fourier Transform) spread, optimum phase condition terms and in addition to that pruned input with one tap scaling is discussed. From this technique starting from simple DFT spread, DFT with phase condition and DFT with precoding offers good reduction in square of crest factor in step-by-step manner than traditional FBMC. Despite not bearing a cyclic prefix, they anticipate lower off-putting discharge. Finally, these schemes are compared in terms of Complexity, rate of error in bits and higher peak power with respect to average to find the optimum one with same properties of conventional FBMC.